Fertility, offspring survival, and adaptive value as related to morphological traits – methodological and interpretation problems - Kościński, Krzysztof (Anthropological Review, 2000)
A great deal of research has been carried out in order to find a relationship between somatic traits and fertility, offspring survival rate and adaptive value. However, the results of these studies lack consistency. The reason behind these discrepancies is the use of inadequate statistical methods and the application of unreliable principles of interpretation. The purpose of this paper is to indicate the methods of data analysis and result interpretation, which permit optimum utilisation of the information contained in a given sample and make it possible to draw the correct conclusions.